Freedom of expression and misinformation laws during the COVID-19 Pandemic and the European court of human rights - Szentgáli-Tóth, Boldizsár (Lex localis, 2023)
This article assesses the European Court of Human Rights’ possible responses to post-COVID-19 misinformation laws. These laws are intended to protect society but may become dangerous weapons if used by governments wishing to silence opponents. We identify four categories of speech restrictions that appeared during the COVID-19 pandemic. We then present the recent misinformation laws from Council of Europe member states as well as various potential arguments when cases appear before the Court, and assess their potential weight. We also analyze the expected post-pandemic development of the European Convention on Human Rights’ Article 10 jurisprudence.
Keywords: constitutional law; emergency; European court of human rights; Evropsko sodišče za človekove pravice; freedom of expression; izredne razmere; pandemic; pandemija; svoboda izražanja; ustavno pravo